Non-invasive Urodynamic Study - The Uroflowmetry - Mallik, Ashraf Uddin; Rahman, Md Mostafizur; Karmaker, Uttam; Jahan, Tamanna; Tabassum, Noushin; Shithee, Shafia Tabassum; Nasrin, Most Jannat E; Samad, Md Abdus (Bangladesh Journal of Urology, 2022)
Abstract not available Bangladesh J. Urol. 2021; 24(1): 105-109